The Dynamics of Research Joint Ventures: A Panel Data Analysis - Tomaso Duso; Enrico Pennings; Jo Seldeslachts (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
The aim of this paper is to test the determinants of Research Joint Ventures' (RJVs) group dynamics. We look at entry, exit and turbulence in RJVs that have been set up under the US National Cooperative Research Act, which allows for certain antitrust exemptions in order to stimulate firms to cooperate in R&D. Accounting for unobserved project characteristics and controlling for inter-RJV interactions and industry effects, the Tobit panel regressions show the importance of group and time features for an RJV's evolution. We further identify an average RJV's long-term equilibrium size and assess its determining factors. Ours is a first attempt to produce robust stylized facts about cooperational short- and long-term dynamics, an important but neglected dimension in research cooperations.
urn:nbn:de:bvb:19-epub-13331-8
Keywords: C23; L24; O32; 330; research joint ventures; dynamics; panel data